2021
DOI: 10.3390/heritage4040224
|View full text |Cite
|
Sign up to set email alerts
|

TEOS-PDMS-Calcium Oxalate Hydrophobic Nanocomposite for Protection and Stone Consolidation

Abstract: A treatment for both protection and consolidation, was synthesized in a simplified procedure through the sol gel process. Synthesized nano-calcium oxalate (CaOx) was incorporated into tetraethoxysilane (TEOS) and polydimethylsiloxane (PDMS), providing a hybrid hydrophobic consolidant nanocomposite. Oxalic acid was selected due to its ability to catalyse the hydrolysis of TEOS, as a drying control agent, but also because of its contribution at the formation of the calcium oxalate in reaction with calcium hydrox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…The nanocomposite reached a good penetration depth inside the stone, without affecting the porosity and pore size distribution, with an improvement of the tensile strength. A further advancement of this formulation was the addition of polydimethylsiloxane (PDMS) to obtain hybrid hydrophobic consolidants, resulting in an increase in the resistance to decay and enhanced mechanical properties of the limestone [67].…”
Section: Nanostructured Materials For Stone Consolidationmentioning
confidence: 99%
“…The nanocomposite reached a good penetration depth inside the stone, without affecting the porosity and pore size distribution, with an improvement of the tensile strength. A further advancement of this formulation was the addition of polydimethylsiloxane (PDMS) to obtain hybrid hydrophobic consolidants, resulting in an increase in the resistance to decay and enhanced mechanical properties of the limestone [67].…”
Section: Nanostructured Materials For Stone Consolidationmentioning
confidence: 99%
“…Through the above dissolution resistant experiment, it is possible to find the effects of the calcium oxalate layer, which provides direction for the sequential application method. This research concentrates on the study of coating densification and crystal regulation, while other research gives more attention to the preparation method, application environment, and performance evaluation [6,27].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, based on the tetraethoxysilane (TEOS) effectiveness as a strengthening agent for Portland cement mortars [28], we synthesized an advanced hydrophobic consolidant, designated as FX-C, using a sol-gel process that combines TEOS, PDMS and nano-calcium oxalate (nano-CaOx) for the preservation of cultural heritage [29,30]. It was found that silicon in TEOS/PDMS copolymer can form strong Si-O bonds with hydroxyl groups of the material for preservation [31].…”
Section: Introductionmentioning
confidence: 99%